EFEKTIVITAS PENGGUNAAN GARAM UNTUK MENCEGAH DAN MENGHAMBAT PERGERAKAN ULAR SANCA BATIK (Python reticulatus) - , GURUH JAYA W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A research on the influence of salt on Phyton reticulatus has been done. It aimed to evaluate the myth stating that salt can cause snakes away. This research involved five Phyton reticulatus. Two methods were used in this research 1) the snakes were placed in a circle of salt, baits were given outside of the circle, 2) snake sprinkled with salt. For the control before the treatment, the snakes were placed on the floor without any salt. It aimed to know the reaction and the behavior of the snakes. The result of this research are 1) snakes with no salt slithered normally, 2) snakes staying in the circle of salt slithered away from the circle after being given baits. The snake ignored the salt. 3) snake scatered over with salt did not make movement or kept staying. It can be concluded that salt does not influence the behavior of Phyton reticulatus.